Drying characteristics and kinetics of fluidized bed dried potato - Bakal, Sushant B; Gedam, Kishor H; Sharma, Gyanendra Prakash (MTT Agrifood Research Finland, 2010)
In developed countries, more than 50% potatoes are consumed as processed products. As drying is the vital phenomenon in processing, it is necessary to investigate the drying characteristics and its kinetics. In this experimental study, drying kinetics of Potato in two different shape of cuboidal & cylindrical with three aspect ratio was investigated as a function of drying conditions. Experiments were conducted using air temperatures of 50, 60 and 70 ºC, at velocity of 7 ms-1. The experimental moisture data were fitted to Page and simple models available in the literature, and a good agreement was observed. The Page model gave better fit than simple model. In the ranges covered, the values of the effective moisture diffusivity, Deff were obtained between 2.278 × 10-9 to 3.314 × 10-8 m2s-1 from the Fick's diffusion model. Using Deff, the value of activation energy (Ea) was determined assuming the Arrhenius-type temperature relationship.
Keywords: Ka; Cuboidal & cylindrical shape; Aspect ratio; drying kinetics; Page's & simple Model